Phase III trial of gemcitabine plus tipifarnib compared with gemcitabine plus placebo in advanced pancreatic cancer - Van Cutsem, Eric; Velde, H. van de; Karasek, P.; Oettle, H.; Vervenne, W. L.; Szawlowski, A.; Schoffski, P.; Post, Stefan; Verslype, C.; Neumann, H.; Safran, H.; Humblet, Y.; et al. (Journal of clinical oncology, 2004)
Purpose: To determine whether addition of the farnesyltransferase inhibitor tipifarnib (Zarnestra, R115777; Johnson and Johnson Pharmaceutical Research and Development, Beerse, Belgium) to standard gemcitabine therapy improves overall survival in advanced pancreatic cancer. Patients and Methods: This randomized, double-blind, placebo-controlled study compared gemcitabine + tipifarnib versus gemcitabine + placebo in patients with advanced pancreatic adenocarcinoma previously untreated with systemic therapy. Tipifarnib was given at 200 mg bid orally continuously; gemcitabine was given at 1,000 mg/m2 intravenously weekly × 7 for 8 weeks, then weekly × 3 every 4 weeks. The primary end point was overall survival; secondary end points included 6-month and 1-year survival rates, progression-free survival, response rate, safety, and quality of life. Results: Six hundred eighty-eight patients were enrolled. Baseline characteristics were well balanced between the two treatment arms. No statistically significant differences in survival parameters were observed. The median overall survival for the experimental arm was 193 v 182 days for the control arm (P = .75); 6-month and 1-year survival rates were 53% and 27% v 49% and 24% for the control arm, respectively; median progression-free survival was 112 v 109 days for the control arm. Ten drug-related deaths were reported for the experimental arm and seven for the control arm. Neutropenia and thrombocytopenia grade ≥ 3 were observed in 40% and 15% in the experimental arm versus 30% and 12% in the control arm. Incidences of nonhematologic adverse events were similar in two groups. Conclusion: The combination of gemcitabine and tipifarnib has an acceptable toxicity profile but does not prolong overall survival in advanced pancreatic cancer compared with single-agent gemcitabine.
Elektronische Reproduktion der Druckausgabe
Gesehen am 31.05.2022